Quality and vitamin A status assessment of different commercial edible oil (Bangladesh Journal of Scientific and Industrial Research, 2019)
The present study was done to evaluate the quality and the vitamin A fortification status of 5 types of commercial edible oils sold in Dhaka city markets. The percentages of free fatty acid (FFA), peroxide value (POV), iodine value (IV) and fatty acid composition were estimated to evaluate the quality and vitamin A content were determined to evaluate the vitamin A fortification status of 25 commercial edible oils- soybean oil, sunflower oil, rice bran oil, mustard oil and palm olein (5 brands of each) . The results revealed that FFA, POV and IV of the commercial oils analyzed were within the BSTI standard limits. The highest saturated fatty acids (SFA) values ranging from 39.85 ± 0.005 to 46.97 ± 0.002 % was found in palm olein samples and the lowest SFA values ranging from 4.56 ± 0.031 to 6.97 ± 0.096 % was found in mustard oils. On the other hand, mustard oils contained highest monounsaturated fatty acids (MUFA) ranging from 69.30 ± 0.189 to 75.87 ± 0.069 % compared to other oils analyzed. Highest polyunsaturated fatty acids (PUFA) were recorded in sunflower oils 64.78 ± 0.035% followed by soybean oils 63.25 ± 0.245%. In addition, except sunflower and mustard oils, vitamin A was found in all the soybean and rice bran oils analyzed. On the contrary, vitamin A was found only in 60% of the palm olein samples analyzed and the content was much lower than the standard value (15-30 ppm).Bangladesh J. Sci. Ind. Res.54(1), 11-20, 2019